Challenges of Clerical Sexual Abuse: Our Family Responsibilities and Collective Action - MADU, Jonathan Chukwuemeka (Nigerian Journal of Peace, Development & Humanitarian Affairs, 2023)
Clerical sexual abuse is a contradiction of life of chastity, an evangelical virtue for Catholic priestly vocation, which one has to observe as a chosen way of life. Yet, in recent years, the Roman Catholic Church worldwide has faced a dramatic increase in allegations of sexual abuse by its clergy, which affects the peace, security, social development and constitutes an abuse of human rights. One long term response has been called to allow clergy to marry but there are reasons to believe that this may not bring about the desired outcome. This article focuses on and explores the challenges as well as argues for family responsibilities in addressing clerical sexual abuse, and after examining the experience of a number of countries, the article suggests collective actions which have the potential to bring about the desired change.